Clinical Utility of 18F‐APN‐1607 Tau PET Imaging in Patients with Progressive Supranuclear Palsy. Issue 10 (5th June 2021) - Li, Ling; Liu, Feng‐Tao; Li, Ming; Lu, Jia‐Ying; Sun, Yi‐Min; Liang, Xiaoniu; Bao, Weiqi; Chen, Qi‐Si; Li, Xin‐Yi; Zhou, Xin‐Yue; Guan, Yihui; Wu, Jian‐Jun; et al.
ABSTRACT: Background: 18 F‐APN‐1607 is a novel tau PET tracer characterized by high binding affinity for 3‐ and 4‐repeat tau deposits. Whether 18 F‐APN‐1607 PET imaging is clinically useful in PSP remains unclear. Objectives: The objective of this study was to investigate the clinical utility of 18 F‐APN‐1607 PET in the diagnosis, differential diagnosis, and assessment of disease severity in patients with PSP. Methods: We enrolled 3 groups consisting of patients with PSP (n = 20), patients with α‐synucleinopathies (MSA with predominant parkinsonism, n = 7; PD, n = 10), and age‐ and sex‐matched healthy controls (n = 13). The binding patterns of 18 F‐APN‐1607 in PET/CT imaging were investigated. Regional standardized uptake ratios were compared across groups and examined in relation to their utility in the differential diagnosis of PSP versus α‐synucleinopathies. Finally, the relationships between clinical severity scores and 18 F‐APN‐1607 uptake were investigated after adjustment for age, sex, and disease duration. Results: Compared with healthy controls, patients with PSP showed increased 18 F‐APN‐1607 binding in several subcortical regions, including the striatum, putamen, globus pallidus, thalamus, subthalamic nucleus, midbrain, tegmentum, substantia nigra, pontine base, red nucleus, raphe nuclei, and locus coeruleus. We identified specific regions that were capable of distinguishing PSP from α‐synucleinopathies. The severity of PSP was positively correlated with the amount of 18 F‐APN‐1607 uptake in the subthalamic nucleus, midbrain, substantia nigra, red nucleus, pontine base, and raphe nuclei. Conclusions: 18 F‐APN‐1607 PET imaging holds promise for the diagnosis, differential diagnosis, and assessment of disease severity in patients with PSP. © 2021 International Parkinson and Movement Disorder Society